2002
DOI: 10.1111/1467-8691.00234
|View full text |Cite
|
Sign up to set email alerts
|

Creativity in Multidisciplinary New Product Development Teams

Abstract: New product development is usually teamwork. Product development teams are created that are cross-functional, representing different functional units, or multidisciplinary, involving several disciplines, or both. In any case, conceiving and developing new products is a joint effort, which means that the traditional view of creativity may not apply. This view, characterized by a focus on individuals as agents of creativity and by the assumption that creativity is a unilateral quality, not a reciprocal or intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 49 publications
0
30
0
3
Order By: Relevance
“…Intrapersonal team characteristics include team members' innovative work behavior (Akgün, Keskin, and Byrne, ; Denison, Hart, and Kahn, ; Vissers and Dankbaar, ), expertise (Ancona and Caldwell, ; Ellemers, De Gilder, and Van den Heuvel, ; Mumin and Elbanna, ), openness (e.g., Aronson, Reilly, and Lynn, ; George and Zhou, ), and customer orientation (Akgün et al., ).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Intrapersonal team characteristics include team members' innovative work behavior (Akgün, Keskin, and Byrne, ; Denison, Hart, and Kahn, ; Vissers and Dankbaar, ), expertise (Ancona and Caldwell, ; Ellemers, De Gilder, and Van den Heuvel, ; Mumin and Elbanna, ), openness (e.g., Aronson, Reilly, and Lynn, ; George and Zhou, ), and customer orientation (Akgün et al., ).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Personal and situational inputs have been conceptualized in a variety of ways. In innovation research, the early stage has been captured by the term 'fuzzy front-end' (Kim & Wilemon, 2002) with individual creativity playing a dominant role (Vissers & Dankbaar, 2002). In entrepreneurship research, early stages have been identified as phases of opportunity identification, planning and marshalling of resources (McGee et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from extensive social network analysis in a large electronics company suggests that by bringing individuals from diverse professions together, diverse teams have the potential to bridge structural holes, or gaps in the flow of knowledge between disconnected professions, which provides access to a great range of knowledge (Burt, 2004) and connects the accumulated knowledge assets of these professional communities (DeDreu & West, 2001;Huang & Newell, 2003;Jehn et al, 1997;Randel & Jaussi, 2003;Vissers & Dankbaar, 2002). As new knowledge often emerges from the recombination of existing ideas (Brown & Duguid, 2001;DeDreu & West, 2001), the process of brokering knowledge across the cognitive boundaries that exist between professional areas frequently triggers innovative ideas and the application of previously disconnected knowledge to new problems.…”
Section: Information/decision-making Perspective On Interprofessionalmentioning
confidence: 99%